Novel pyrazine derivative-functionalized phthalocyanines as multifunctional agents for sono/photochemical and antimicrobial applications - Sustan, Hakan; Gunsel, Armagan; Gokcil, Gokce; Atmaca, Goknur Yasa; Tuzun, Burak; Aydemir, Ozlem; Gunsel, Hilal; Bilgicli, Ahmet T.; Erdogmus, Ali; Yarasir, M. Nilufer (ELSEVIER SCIENCE SA, 2026)
In this study, the novel 4-(2-(pyrazin-2-yl) ethylthio) phthalonitrile (1) was synthesized as the starting material by reacting 4-nitrophthalonitrile with 2-(pyrazin-2-yl) ethanethiol. Using this intermediate, the peripherally tetra-pyrazine derivative-substituted phthalocyanine compounds (2,3) were synthesized for the first time. Subsequently, their water-soluble quaternized phthalocyanine derivatives (2a,3a) were prepared. All compounds used were characterized with various spectroscopic methods such as UV-Vis, FT-IR, 1H NMR, 13C NMR and MALDI-TOF MS. This study investigates the efficiency of photochemical and sono-photochemical approaches in boosting singlet oxygen generation, a key factor in photodynamic therapy applications. The synthesized phthalocyanines exhibited notable singlet oxygen quantum yields. Specifically, the phthalocyanines (2,3,2a,3a) achieved Phi Delta values of 0.64, 0.75, 0.18, and 0.21 under photochemical applications, and 0.77, 0.97, 0.27, and 0.39 under sono-photochemical applications, respectively. The antimicrobial activities of these compounds were evaluated by the broth microdilution method against a panel of Gram-positive and Gram-negative bacteria, including Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Enterococcus faecalis, and Klebsiella pneumoniae. The results revealed that quaternization significantly improved the antibacterial performance. While compounds (2) and (3) exhibited MIC values in the range of 16-32 mu g/mL, their quaternized analogues (2a) and (3a) demonstrated stronger inhibitory effects, with compound (3a) showing the highest potency (MIC: 4-8 mu g/ mL) across all tested strains. These findings highlight the potential of pyrazine-functionalized quaternized phthalocyanines as promising candidates for the development of novel antimicrobial agents. Gaussian software was used to calculate the ligand and metal complexes of phthalocyanine (Pc) derivatives (2,3,2a,3a) in 6-31 g and 6-31++g(d,p) basis sets at the B3LYP, HF, and M062X levels. The compounds' effects against different proteins were then contrasted, and their interactions were examined.
Keywords: Phthalocyanine; Synthesis; Sono/photochemical; Antimicrobial; DFT; ESCHERICHIA-COLI; ANTIOXIDANT; METALLOPHTHALOCYANINES; AGGREGATION; CHLORIDE; Chemistry